2013
DOI: 10.4236/me.2013.41010
|View full text |Cite
|
Sign up to set email alerts
|

Banking Sector and Monetary Policy Transmission: Bank Capital, Credit and Risk-Taking Channels

Abstract: In the literature, the question of central banks' responsibility for triggering crises is raised when sustainable low interest rates lead to excessive banks' risk exposures. However, such portfolio choices mainly depend on the various returns of assets and on the official interest rate, taking into account that the bank lending channel is affected by the bank capital channel. On the basis of a simple theoretical model including a solvency ratio, we show that during recessions a credit rationing is observed tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Risk aversion explains this evolution. Gilles et al, 2013, arrive at the same conclusion; they concluded that during expansion phases, monetary policy can induce failure in credit activity and increase in financial instability; on the contrary, during recessions, banks tend to credit rationing and quality of credits. Authors suggest the necessity of cooperation between central banks and micro prudential supervision.…”
Section: Previous Resultsmentioning
confidence: 63%
“…Risk aversion explains this evolution. Gilles et al, 2013, arrive at the same conclusion; they concluded that during expansion phases, monetary policy can induce failure in credit activity and increase in financial instability; on the contrary, during recessions, banks tend to credit rationing and quality of credits. Authors suggest the necessity of cooperation between central banks and micro prudential supervision.…”
Section: Previous Resultsmentioning
confidence: 63%
“…The core model presented in this paper departs from Gilles, Gauvin, & Huchet (2013) essentially by using an analysis based on the observation of the balance sheet of the banking sector. Here, we added a differentiated analysis of bank categories according to their initial characteristics.…”
Section: Outline Of the Modelmentioning
confidence: 99%
“…In the next section, the banks' characteristics, that can influence the relationship between monetary policy and banks, are identified. The third section outlines a theoretical model developed in Gilles, Gauvin, & Huchet (2013). Next, the model is extended by including banks' characteristics, and especially banks' equities and liquidity.…”
Section: Introductionmentioning
confidence: 99%
“…If some Bonds, as German, continue to represent a safe haven, other Bonds, which have bad performance (Greece, Ireland), are neglected. The flight to quality in Eurozone actually plays an important role but occurs in the form of a rise in deposit facilities (Gilles et al, 2013) (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%